Computational studies of soot paths to cylinder wall layers of a direct injection diesel engine - Wan Mahmood, Wan Mohd Faizal (2011)
The investigation reported in this thesis is concerned with the topic of soot formation and soot particle motion in the cylinder of a light duty automotive diesel engine. CFD has been employed to simulate in-cylinder conditions and to investigate the source of particles which are transferred to the oil. The accumulation of soot in the lubricating oil of diesel engines is one of the factors limiting the interval between oil changes and hence service interval. Soot particles can be transferred to oil film on the cylinder wall layers through the complex motion of the fluid flow in the cylinder. The paths of soot particles from specific in-cylinder locations and crank angle instants have been explored using the results for cylinder charge motion predicted by the Kiva-3v CFD code. Using the velocity fields from the simulation data, massless tracking of the in-cylinder soot particles in space and time is carried out employing a particle tracking with trilinear interpolation technique. From this investigation, new computational codes for the prediction of soot particle paths and soot particle size change along a specific path in a diesel engine have been developed. This investigation is the first numerical study into soot particle trajectories within an engine and thus opens up a novel branch of research of soot formation within internal combustion engines.